Preparation method of CO-SCR denitration catalyst, CO-SCR denitration catalyst and flue gas denitration method
By preparing high-performance CO-SCR denitrification catalysts, ball milling and impregnation technology are used to improve the denitrification efficiency of the catalyst under oxygen-rich conditions, the problems of poor performance and high cost of catalysts in the prior art are solved, and efficient and low-cost flue gas denitrification effect are achieved.
Patent Information
- Application Number
- CN202411442492.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2044-10-16
AI Technical Summary
The existing CO-SCR denitrification catalysts have poor performance under oxygen-rich conditions and are highly prepared, which cannot meet the needs of industrial applications.
By mixing the primary carbonization material with the adhesive solution ball mill to form activated carbon, and a high-performance CO-SCR denitrification catalyst is prepared by impregnating active components such as soluble transition metal salts and flavonoids.
The denitrification efficiency of the catalyst under oxygen-rich conditions is improved, the preparation cost is reduced, and the compressive strength and stability of activated carbon are significantly improved, extending the service life.
Smart Images

Figure CN118950086B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of flue gas denitration, and in particular to a preparation method of a CO-SCR denitration catalyst, a CO-SCR denitration catalyst and a flue gas denitration method. Background Art
[0002] Among flue gas denitrification technologies, SCR is currently the most effective, mature and widely used technology. The use of SCR technology can achieve a denitrification efficiency of 80-90% at low temperatures. As one of the flue gases, CO is also an important reducing agent. It can remove NOx from flue gas through CO selective catalytic reduction to generate pollution-free CO2 and N2, avoiding problems such as ammonia escape and pipeline corrosion. Since the use of CO as a reducing agent can save production and transportation costs and has good economic benefits, the development of CO-SCR technology and its industrialization is a very promising research direction. However, in current research, most of the research on CO-SCR denitrification is carried out under oxygen-free or 5% oxygen content conditions, which is not suitable for 15-20% oxygen content conditions in real flue gas atmospheres. Under real flue gas conditions, CO is easily oxidized to CO2 by O2 at a lower temperature, which cannot match the reaction temperature of NOx catalytic reduction, resulting in a very low catalyst denitrification efficiency. How to improve the performance of CO-SCR denitrification catalysts under oxygen-rich conditions is a problem that needs to be solved urgently.
[0003] The Chinese invention patent application with publication number CN117324026A discloses a metal compound CO-SCR catalyst encapsulated in a silicon-aluminum zeolite molecular sieve and its preparation and application. The method encapsulates iridium and rubidium into the silicon-aluminum zeolite molecular sieve to obtain a denitration efficiency of 85% at 5% oxygen content and 270°C. However, since the active components used are precious metals and the preparation process is complicated, the cost is relatively high. The Chinese invention patent with publication number CN111229212B discloses a CO-SCR denitration catalyst prepared by co-precipitating ammonium cerium nitrate and manganese nitrate and encapsulating them into an aluminum zeolite molecular sieve. The denitration efficiency is 84% at 5% oxygen content and 250°C. It has the advantages of low preparation cost and high efficiency, but its performance is poor under oxygen-rich conditions.
[0004] Therefore, there is currently no low-cost, high-performance CO-SCR catalyst that can overcome oxygen-rich conditions. In addition, in actual use, activated carbon-based catalysts also face the problem of fragmentation and failure. Summary of the invention
[0005] The main purpose of the present invention is to provide a preparation method of a CO-SCR denitration catalyst, a CO-SCR denitration catalyst and a flue gas denitration method, so as to solve the technical problem that there is no high-performance CO-SCR catalyst with high strength, low cost and the ability to overcome oxygen-rich conditions in the prior art.
[0006] In order to achieve the above object, according to the first aspect of the present invention, a method for preparing a CO-SCR denitration catalyst is provided, and the technical scheme is as follows:
[0007] The preparation method of the CO-SCR denitration catalyst comprises the following steps:
[0008] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material;
[0009] The mixed material, the reinforcing resin powder and the second binder solution are ball-milled and then extruded to obtain a compact;
[0010] The pressed green body is activated to obtain activated carbon;
[0011] The activated carbon is immersed in a first modification solution, and after the immersion is completed, the activated carbon is filtered, dried and calcined to obtain modified activated carbon; the first modification solution contains a soluble transition metal salt;
[0012] The modified activated carbon is immersed in a second modification solution, and after the immersion is completed, the solution is filtered and dried to obtain a CO-SCR denitration catalyst; the second modification solution contains flavonoid compounds or glycosides of flavonoid compounds;
[0013] The fluidity of the first adhesive is 20-50 mPa·s; and the bonding strength of the second adhesive solution is 1.5-3.5 MPa.
[0014] As a further improvement of the preparation method of the above-mentioned CO-SCR denitrification catalyst: the primary carbonized material is obtained by carbonizing the biomass raw material at 500-600°C for 1-2 hours in an oxygen-free environment and then grinding and screening; the activation treatment is to activate the pressed billet in a CO2 atmosphere at 700-800°C for 2-3 hours.
[0015] As a further improvement of the preparation method of the above-mentioned CO-SCR denitrification catalyst: the reinforced resin powder is at least one of phenolic resin, polyvinyl acetate, cyanoacrylate, polyurethane resin, epoxy resin, acrylic resin, polystyrene resin, polyetheretherketone resin, polypropylene resin, and modified polyester resin; the amount of the reinforced resin powder is 1 to 3% of the amount of the mixture.
[0016] As a further improvement of the preparation method of the above-mentioned CO-SCR denitrification catalyst: the soluble transition metal salt is a cobalt salt, a cerium salt and a manganese salt; the molar ratio of the cobalt element, the cerium element and the manganese element in the first modified solution is 1:(1-5):(1-5); the total mass of the cobalt element, the cerium element and the manganese element in the first modified solution is 20-30% of the mass of the activated carbon; the activated carbon is immersed in the first modified solution for 5-10 hours by an equal volume impregnation method; the calcination temperature is 250-300°C, and the calcination time is 3-5 hours.
[0017] As a further improvement of the preparation method of the above-mentioned CO-SCR denitrification catalyst: the second modified solution contains at least one of luteolin, quercetin, quercetin, isoquercetin, naringin, baicalin, and flavonols; the mass of the solute in the second modified solution is 1 to 2% of the mass of the modified activated carbon; and the activated carbon is immersed in the second modified solution for 12 to 24 hours by an equal volume impregnation method.
[0018] As a further improvement of the preparation method of the above-mentioned CO-SCR denitration catalyst: firstly, the modified activated carbon is immersed in a glutaraldehyde solution for 1 to 2 hours, filtered and washed with water, and then immersed in a second modified solution.
[0019] As a further improvement of the above-mentioned preparation method of CO-SCR denitrification catalyst: the first adhesive solution is an aqueous solution of at least one of sodium carboxymethyl cellulose, polyethylene oxide, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose, gum arabic, and xanthan gum; 200 to 400 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material.
[0020] As a further improvement of the above-mentioned preparation method of CO-SCR denitrification catalyst: the second adhesive solution is an aqueous solution of at least one of syrup, starch paste, polyvinyl alcohol, chitosan, white latex, and dextrin; 100 to 300 mL of the second adhesive solution is added to every 1 kg of the mixture.
[0021] In order to achieve the above object, according to the second aspect of the present invention, a CO-SCR denitration catalyst is provided, and the technical scheme is as follows:
[0022] The CO-SCR denitration catalyst is prepared by the preparation method described in the first aspect above.
[0023] In order to achieve the above object, according to the third aspect of the present invention, a flue gas denitrification method is provided, and the technical scheme is as follows:
[0024] The flue gas denitration method uses the CO-SCR denitration catalyst prepared by the preparation method described in the first aspect to denitrate the flue gas.
[0025] The preparation method of the CO-SCR denitration catalyst, the CO-SCR denitration catalyst and the flue gas denitration method of the present invention have the following advantages:
[0026] (1) The applicant has found that in the process of preparing activated carbon, the fluidity and bonding strength of the adhesive solution are two key parameters that will significantly affect the quality and performance of the final product. It has been found through experiments that when the fluidity of the first adhesive solution is high, it can ensure that it can fully penetrate and coat the primary carbonized material to form a uniform mixture, which is particularly important for the strength of the activated carbon; at the same time, when the bonding strength of the second adhesive solution is high, it can ensure that a green body with sufficient mechanical strength is formed during the green pressing process, thereby ensuring the strength of the final activated carbon. Therefore, the present invention significantly improves the compressive strength of the activated carbon by improving the fluidity and bonding strength of the first adhesive solution and the second adhesive solution.
[0027] (2) The present invention also adds reinforced resin powder to the green body, which can improve the mechanical strength of the activated carbon material and make it more resistant to wear and cracking during use; the reinforced resin powder can improve the molding properties of the mixture, provide better adhesion and plasticity during the extrusion molding process, and enable the pressed green body to be molded more uniformly and stably; in the subsequent high-temperature activation treatment process, the reinforced resin powder can improve the thermal stability of the material and reduce the damage to the material structure caused by high-temperature treatment, thereby maintaining the structural integrity and pore structure of the activated carbon; the reinforced resin powder may also have certain chemical properties that can form a more stable combination with active components such as transition metal oxides and flavonoid compounds, thereby improving the adsorption performance of the denitrification catalyst.
[0028] (3) Under the combined action of the first binder solution, the second binder solution and the reinforcing resin powder, the high-load transition metal oxides are more easily fixed by the pore structure of the activated carbon and are not easily agglomerated, so that the high-load active components have good stability and dispersibility. At the same time, the calcination effect increases the lattice oxygen content on the surface of the material. The lattice oxygen on the surface of the material and the active components work together to make the surface of the activated carbon have a high surface oxygen exchange rate during the denitration process, which effectively accelerates the dissociation rate of NOx molecules and the reduction rate of CO, so that NOx reacts preferentially with CO, thereby improving the denitration efficiency of the material under oxygen-rich conditions.
[0029] (4) Flavonoids are a class of polyphenolic compounds with diverse structures and functions. They can introduce groups such as hydroxyl (-OH), carboxyl (-COOH), amino (-NH2), thiol (-SH), and sulfonic acid (-SO3H). These functional groups can increase the active sites on the surface of activated carbon, which is beneficial to the adsorption and reaction of nitrogen oxides (NOx). Functional groups such as phenolic hydroxyl and hydroxyl can react chemically with NOx, which helps to convert NOx into harmless substances such as nitrogen (N2) and water (H2O), thereby enhancing the catalytic performance of activated carbon in the denitrification process. Most flavonoids have excellent antioxidant properties, which helps to maintain the long-term stability and activity of activated carbon. In high temperature or strong oxidizing environment, the modified activated carbon is not prone to oxidative degradation, thereby extending its service life. It can be seen that the present invention uses flavonoids to modify activated carbon to enhance adsorption capacity, biocompatibility and antioxidant properties.
[0030] It can be seen that the preparation method of the CO-SCR denitration catalyst, the CO-SCR denitration catalyst and the flue gas denitration method of the present invention provide a CO-SCR denitration catalyst with high strength, low cost, good antioxidant performance and very suitable for flue gas denitration, as well as its preparation method and application, which effectively solves the technical problem that there is no high-performance CO-SCR catalyst with high strength, low cost and the ability to overcome oxygen-rich conditions in the prior art.
[0031] The following is a further description of the embodiments of the invention provided in this specification in conjunction with the accompanying drawings and specific implementation methods. Additional aspects and advantages of the embodiments of the invention provided in this specification will be partially given in the following description, and partially will become apparent from the following description, or will be understood through the practice of the embodiments of the invention provided in this specification. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] The drawings that constitute part of the embodiments of the inventions provided in this specification are used to assist in understanding the embodiments of the inventions provided in this specification. The contents provided in the drawings and the related descriptions in the embodiments of the inventions provided in this specification can be used to explain the embodiments of the inventions provided in this specification, but do not constitute improper limitations on the embodiments of the inventions provided in this specification. In the drawings:
[0033] Figure 1 This is a schematic diagram of the structure of the catalyst denitration performance evaluation device used in the present invention.
[0034] Figure 2 This is a SEM photograph of the CO-SCR denitration catalyst of Example 4 of the present invention.
[0035] Figure 3 This is a pore size distribution diagram of the CO-SCR denitration catalyst of Example 4 of the present invention. DETAILED DESCRIPTION
[0036] The following is a clear and complete description of the embodiments of the inventions provided in this specification in conjunction with the accompanying drawings. A person of ordinary skill in the art will be able to implement the embodiments of the inventions provided in this specification based on these descriptions. Before describing the embodiments of the inventions provided in this specification in conjunction with the accompanying drawings, it should be particularly noted that:
[0037] The technical solutions and technical features provided in each part of the embodiments of the invention provided in this specification, including the following description, may be combined with each other if there is no conflict.
[0038] In addition, the embodiments of the inventions provided in this specification involved in the following descriptions are generally only part of the embodiments of the inventions provided in this specification rather than all of the embodiments. Therefore, based on the embodiments of the inventions provided in this specification, all other embodiments obtained by ordinary technicians in this field without making any creative work should fall within the scope of protection of the embodiments of the inventions provided in this specification.
[0039] Regarding the terms and units in the embodiments of the inventions provided in this specification: The terms "including", "comprising", "having" and any variations thereof in the descriptions and claims of the embodiments of the inventions provided in this specification and in the related parts are intended to cover non-exclusive inclusions. In addition, other relevant terms and units in the embodiments of the inventions provided in this specification can be reasonably interpreted based on the relevant contents of the embodiments of the inventions provided in this specification.
[0040] Figure 1 This is a schematic diagram of the structure of the catalyst denitration performance evaluation device used in the present invention. Figure 1 The catalyst denitration performance evaluation device shown is used to test the denitration performance of the CO-SCR denitration catalysts of the following examples and comparative examples.
[0041] like Figure 1 As shown, N2, NO, O2, and CO are mixed in a gas mixing bottle to form a mixed gas, in which the NO concentration is 500ppm, the O2 concentration is 10%, the CO concentration is 2500ppm, and the air velocity is 5000h -1 The mixed gas passes through the reaction bed filled with CO-SCR denitration catalyst at a flow rate of 2.5L / min, and the bed reaction temperature is 250℃. The NO concentration in the tail gas passing through the reaction bed is measured by an infrared flue gas analyzer and recorded as C NO , and then use the formula "NO removal rate = (1-C NO / 500)×100%” to calculate the NO removal rate.
[0042] Example 1: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0043] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a hydroxypropyl methylcellulose solution with a fluidity of 40 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0044] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a chitosan solution with a bonding strength of 2.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a phenolic resin, and its amount is 2% of the amount of the mixed material.
[0045] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0046] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. Among them, the first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:1:1, and the total mass of cobalt element, cerium element and manganese element is 20% of the mass of activated carbon. The activated carbon is placed in the first modification solution and impregnated for 8 hours using the equal volume impregnation method. The roasting temperature is 250°C and the roasting time is 3 hours.
[0047] The modified activated carbon is immersed in the second modification solution, filtered and dried after the immersion is completed, and a CO-SCR denitration catalyst is obtained. The second modification solution is an ethanol solution of quercetin and quercetin, the masses of quercetin and quercetin are equal and the total mass is 1% of the mass of the modified activated carbon. The activated carbon is immersed in the second modification solution for 12 hours by an equal volume impregnation method.
[0048] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 259N / cm, the iodine value was 989mg / g, and the NO removal rate was 98.6%.
[0049] Example 2: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0050] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a gum arabic solution with a fluidity of 20 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0051] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a polyvinyl alcohol solution with a bonding strength of 3 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a polyurethane resin, and its amount is 2% of the amount of the mixed material.
[0052] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0053] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. Among them, the first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:5:5, and the total mass of cobalt element, cerium element and manganese element is 30% of the mass of activated carbon. The activated carbon is placed in the first modification solution and impregnated for 8 hours using the equal volume impregnation method. The roasting temperature is 300°C and the roasting time is 3 hours.
[0054] The modified activated carbon is immersed in the second modification solution, filtered and dried after the immersion is completed, and a CO-SCR denitration catalyst is obtained. The second modification solution is an ethanol solution of quercetin and quercetin, the masses of quercetin and quercetin are equal and the total mass is 1% of the mass of the modified activated carbon. The activated carbon is immersed in the second modification solution for 12 hours by an equal volume impregnation method.
[0055] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 252N / cm, the iodine value was 1003mg / g, and the NO removal rate was 98.9%.
[0056] Example 3: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0057] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a xanthan gum solution with a fluidity of 50 mPa·s, and 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0058] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a white latex solution with a bonding strength of 3.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is an epoxy resin, and its amount is 1% of the amount of the mixed material.
[0059] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0060] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. Among them, the first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:3:4, and the total mass of cobalt element, cerium element and manganese element is 20% of the mass of activated carbon. The activated carbon is placed in the first modification solution and impregnated for 8 hours using the equal volume impregnation method. The roasting temperature is 250°C and the roasting time is 5 hours.
[0061] The modified activated carbon is immersed in the second modified solution, filtered and dried after the immersion is completed, and a CO-SCR denitration catalyst is obtained. The second modified solution is an aqueous solution of naringin and baicalin, the mass of naringin and baicalin is equal and the total mass is 1% of the mass of the modified activated carbon. The activated carbon is immersed in the second modified solution for 12 hours by an equal volume impregnation method.
[0062] The test results show that the compressive strength of the CO-SCR denitrification catalyst is 250N / cm, the iodine value is 1021mg / g, and the NO removal rate is 99.3%.
[0063] Example 4: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0064] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a sodium carboxymethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0065] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a polyvinyl alcohol solution with a bonding strength of 3 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a phenolic resin, and its amount is 2% of the amount of the mixed material.
[0066] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0067] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. The first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:1:2, and the total mass of cobalt element, cerium element and manganese element is 25% of the mass of activated carbon. The activated carbon is immersed in the first modification solution for 8 hours by using the equal volume impregnation method. The roasting temperature is 300°C and the roasting time is 5 hours.
[0068] The modified activated carbon is immersed in the second modified solution, filtered and dried after the immersion is completed, and a CO-SCR denitration catalyst is obtained. The second modified solution is an aqueous solution of naringin and baicalin, the mass of naringin and baicalin is equal and the total mass is 1% of the mass of the modified activated carbon. The activated carbon is immersed in the second modified solution for 12 hours by an equal volume impregnation method.
[0069] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 264N / cm, the iodine value was 972mg / g, and the NO removal rate was 99.2%.
[0070] Example 5: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0071] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a sodium carboxymethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0072] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a sugarcane molasses solution with a bonding strength of 1.5 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is an acrylic resin, and its amount is 3% of the amount of the mixed material.
[0073] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0074] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. The first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:2:3, and the total mass of cobalt element, cerium element and manganese element is 30% of the mass of activated carbon. The activated carbon is placed in the first modification solution and impregnated for 8 hours using the equal volume impregnation method. The roasting temperature is 250°C and the roasting time is 3 hours.
[0075] The modified activated carbon is immersed in the second modification solution, filtered and dried after the immersion is completed, and a CO-SCR denitration catalyst is obtained. The second modification solution is an aqueous solution of naringin and baicalin, the mass of naringin and baicalin is equal and the total mass is 2% of the mass of the modified activated carbon. The activated carbon is immersed in the second modification solution for 12 hours by an equal volume impregnation method.
[0076] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 246N / cm, the iodine value was 1074mg / g, and the NO removal rate was 99.5%.
[0077] Example 6: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0078] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a hydroxyethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0079] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a dextrin solution with a bonding strength of 2 MPa; 200 mL of the second adhesive solution is added to every 1 kg of the mixed material. The reinforcing resin powder is a polystyrene resin, and its amount is 2% of the amount of the mixed material.
[0080] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0081] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. The first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:4:3, and the total mass of cobalt element, cerium element and manganese element is 25% of the mass of activated carbon. The activated carbon is immersed in the first modification solution for 8 hours by the equal volume impregnation method. The roasting temperature is 300°C and the roasting time is 3 hours.
[0082] The modified activated carbon was immersed in the second modification solution, filtered and dried after the immersion, and the CO-SCR denitration catalyst was obtained. The second modification solution was an ethanol solution of luteolin and naringin, the mass of luteolin and naringin was equal and the total mass was 2% of the mass of the modified activated carbon. The activated carbon was immersed in the second modification solution for 12 hours by using the equal volume impregnation method.
[0083] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 248N / cm, the iodine value was 1044mg / g, and the NO removal rate was 99.5%.
[0084] Example 7: A CO-SCR denitration catalyst and a preparation method thereof include the following steps:
[0085] The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material. The first adhesive is a hydroxyethyl cellulose solution with a fluidity of 30 mPa·s. 300 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material. The primary carbonized material is obtained by grinding and sieving the biomass raw material after carbonizing it at 550°C for 2 hours without oxygen;
[0086] The mixed material, the reinforcing resin powder and the second adhesive solution are ball-milled and mixed, and then extruded to obtain a compact. The second adhesive solution is a starch paste solution with a bonding strength of 2MPa; 200mL of the second adhesive solution is added to every 1kg of the mixed material. The reinforcing resin powder is a polypropylene resin, and its amount is 3% of the amount of the mixed material.
[0087] The pressed green body was activated in a CO2 atmosphere at 750°C for 3 h to obtain activated carbon.
[0088] The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and roasted to obtain modified activated carbon. The first modification solution is a mixed solution of cobalt nitrate, cerium nitrate and manganese nitrate, the molar ratio of cobalt element, cerium element and manganese element is 1:2:2, and the total mass of cobalt element, cerium element and manganese element is 25% of the mass of activated carbon. The activated carbon is placed in the first modification solution and impregnated for 8 hours using the equal volume impregnation method. The roasting temperature is 250°C and the roasting time is 5 hours.
[0089] The modified activated carbon was immersed in the second modification solution, filtered and dried after the immersion, and the CO-SCR denitration catalyst was obtained. The second modification solution was an ethanol solution of luteolin and naringin, the mass of luteolin and naringin was equal and the total mass was 2% of the mass of the modified activated carbon. The activated carbon was immersed in the second modification solution for 12 hours by using the equal volume impregnation method.
[0090] The test showed that the compressive strength of the CO-SCR denitrification catalyst was 244N / cm, the iodine value was 1135mg / g, and the NO removal rate was 99.6%.
[0091] An embodiment of the flue gas denitration method of the present invention is to perform denitration treatment on the flue gas using the CO-SCR denitration catalyst prepared by the preparation method described in any one of the above embodiments.
[0092] Comparative Example 1: Compared with Example 4, the CO-SCR denitration catalyst and its preparation method of this comparative example are different in that the modified activated carbon is first placed in a glutaraldehyde solution with a mass fraction of 1.5%, filtered and washed with water after immersion for 1 hour, and then immersed in a second modified solution. The test results show that the compressive strength of the CO-SCR denitration catalyst is 261N / cm, the iodine value is 1124mg / g, and the NO removal rate is 99.8%.
[0093] Comparative Example 2: Compared with Example 4, the CO-SCR denitration catalyst and its preparation method of this comparative example are different in that the second modified solution is not used for impregnation modification. The test results show that the compressive strength of the CO-SCR denitration catalyst is 266N / cm, the iodine value is 927mg / g, and the NO removal rate is 96.6%.
[0094] Comparative Example 3: Compared with Example 4, the CO-SCR denitration catalyst and its preparation method of this comparative example are different in that no reinforced resin powder is used. The test results show that the compressive strength of the CO-SCR denitration catalyst is 235N / cm, the iodine value is 962mg / g, and the NO removal rate is 97.1%.
[0095] Comparative Example 4: Compared with Example 2, the CO-SCR denitration catalyst and its preparation method in this comparative example are different in that the first adhesive is a gum arabic solution with a fluidity of 15 mPa·s. The test results show that the compressive strength of the CO-SCR denitration catalyst is 235 N / cm, the iodine value is 979 mg / g, and the NO removal rate is 97.3%.
[0096] Comparative Example 5: Compared with Example 3, the CO-SCR denitration catalyst and its preparation method in this comparative example have the following differences: the first adhesive is a polyethylene oxide solution with a fluidity of 55 mPa·s. The test results show that the compressive strength of the CO-SCR denitration catalyst is 227 N / cm, the iodine value is 956 mg / g, and the NO removal rate is 96.9%.
[0097] Comparative Example 6: Compared with Example 5, the CO-SCR denitration catalyst and its preparation method of this comparative example have the following differences: the second adhesive solution is a sugarcane molasses solution, and the bonding strength is 1.2MPa. The test results show that the compressive strength of the CO-SCR denitration catalyst is 231N / cm, the iodine value is 977mg / g, and the NO removal rate is 98.1%.
[0098] Comparative Example 7: Compared with Example 3, the CO-SCR denitration catalyst and its preparation method in this comparative example have the following differences: the second adhesive solution is a white latex solution, and the bonding strength is 3.7 MPa. The test results show that the compressive strength of the CO-SCR denitration catalyst is 249 N / cm, the iodine value is 988 mg / g, and the NO removal rate is 98.2%.
[0099] Figure 2 : is a SEM photo of the CO-SCR denitration catalyst of Example 4 of the present invention. Figure 2As shown, the CO-SCR denitrification catalyst presents a porous structure. On the basis of more macropores, there are a large number of mesopores and micropores, among which a large number of particles are dispersed and attached on the surface of the macropores and the surface of the material, indicating that the metal oxides are successfully loaded on the activated carbon carrier and are relatively evenly distributed.
[0100] Figure 3 : is the pore size distribution diagram of the CO-SCR denitration catalyst of Example 4 of the present invention. Figure 2 As shown, the average pore diameter of the CO-SCR denitration catalyst is 3.1509 nm, there is a certain pore size distribution between 0.3 and 0.75 mm, and there are also a certain number of mesopores distributed between 2 and 2.5 nm.
[0101] Combination Figure 2 and Figure 3 The results show that the rich pore structure and active components work together to facilitate the efficient adsorption and dissociation of NO, thereby promoting the CO-SCR efficiency of the CO-SCR denitrification catalyst under oxygen-rich conditions.
[0102] The fluidity of the adhesive is tested using the "Method for Determination of Viscosity of Adhesives" (GB / T 2794-2022). The higher the viscosity value, the lower the fluidity.
[0103] The bonding strength of the adhesive is tested using the "Determination of tensile shear strength of adhesives (rigid material to rigid material)" (GB / T 7124-2008). The greater the tensile shear strength value, the greater the bonding strength.
[0104] The compressive strength was tested using the “Test method for wood activated carbon - Determination of strength” (GB / T 12496.6-1999).
[0105] The iodine value test is carried out according to the "Test method for wood activated carbon - Determination of iodine adsorption value" (GB / T 12496.8-1999).
[0106] The above is a description of the relevant contents of the embodiments of the inventions provided in this specification. Based on these descriptions, a person of ordinary skill in the art will be able to implement the embodiments of the inventions provided in this specification. Based on the above contents of the embodiments of the inventions provided in this specification, all other preferred implementations and embodiments obtained by a person of ordinary skill in the art without making any creative work shall fall within the scope of protection of the embodiments of the inventions provided in this specification.
Claims
1. A method for preparing a CO-SCR denitration catalyst, characterized in that: The following steps are involved: The primary carbonized material and the first adhesive solution are ball-milled to obtain a mixed material; The mixed material, the reinforcing resin powder and the second binder solution are ball-milled and then extruded to obtain a compact; The pressed green body is activated to obtain activated carbon; The activated carbon is impregnated in the first modification solution, and after the impregnation is completed, it is filtered, dried and calcined to obtain modified activated carbon; The first modified solution contains a soluble transition metal salt; The modified activated carbon is immersed in a second modification solution, and after the immersion is completed, the solution is filtered and dried to obtain a CO-SCR denitration catalyst; the second modification solution contains flavonoid compounds or glycosides of flavonoid compounds; The fluidity of the first adhesive is 20-50 mPa·s; and the bonding strength of the second adhesive solution is 1.5-3.5 MPa.
2. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The primary carbonized material is obtained by carbonizing the biomass raw material at 500-600°C for 1-2 hours in an oxygen-free environment and then grinding and screening it; the activation treatment is to activate the pressed green sheet in a CO2 atmosphere at 700-800°C for 2-3 hours.
3. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The reinforcing resin powder is at least one of phenolic resin, polyvinyl acetate, cyanoacrylate, polyurethane resin, epoxy resin, acrylic resin, polystyrene resin, polyetheretherketone resin, polypropylene resin and modified polyester resin; the amount of the reinforcing resin powder is 1-3% of the mass of the mixture.
4. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The soluble transition metal salts are cobalt salts, cerium salts and manganese salts; the molar ratio of cobalt element, cerium element and manganese element in the first modified solution is 1:(1-5):(1-5); the total mass of cobalt element, cerium element and manganese element in the first modified solution is 20-30% of the mass of activated carbon; the activated carbon is immersed in the first modified solution for 5-10 hours by an equal volume impregnation method; the calcination temperature is 250-300°C, and the calcination time is 3-5 hours.
5. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The second modified solution contains at least one of luteolin, quercetin, quercetin, isoquercetin, naringin, baicalin, and flavonols; the mass of the solute in the second modified solution is 1-2% of the mass of the modified activated carbon; and the activated carbon is immersed in the second modified solution for 12-24 hours using an equal volume impregnation method.
6. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: First, the modified activated carbon is immersed in a glutaraldehyde solution for 1 to 2 hours, filtered and washed with water, and then immersed in a second modification solution.
7. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The first adhesive solution is an aqueous solution of at least one of sodium carboxymethyl cellulose, polyethylene oxide, hydroxypropyl methyl cellulose, methyl cellulose, hydroxyethyl cellulose, gum arabic and xanthan gum; 200-400 mL of the first adhesive solution is added to every 1 kg of the primary carbonized material.
8. The method for preparing a CO-SCR denitration catalyst according to claim 1, characterized in that: The second adhesive solution is an aqueous solution of at least one of syrup, starch paste, polyvinyl alcohol, chitosan, white latex, and dextrin; 100 to 300 mL of the second adhesive solution is added to every 1 kg of the mixture. 9.CO-SCR denitration catalyst, characterized by: The compound is prepared by the preparation method according to any one of claims 1 to 8.
10. A flue gas denitrification method, characterized in that: The flue gas is denitrated using the CO-SCR denitration catalyst prepared by the preparation method according to any one of claims 1 to 8.
Citation Information
Patent Citations
A CO-SCR denitrification catalyst, its preparation method and application
CN111229212B
Silicon-aluminum zeolite molecular sieve packaged intermetallic compound CO-SCR catalyst as well as preparation and application thereof
CN117324026A
Method for preparing natural antioxidant and application thereof in tea oil
CN102150923A
Preparation method of coated nano zero-valent iron taking multilayer activated-carbon-coated graphene oxide composite powder as carrier
CN104587956A